O DIREITO À EDUCAÇÃO DE QUALIDADE: UM DIREITO FUNDAMENTAL - EDUARDA SILVA MARTINS , MARIA; LOEBLEIN DOS SANTOS , MARCELO; PEDIRIVA , MATEUS; CRISTINA DE OLIVEIRA , MARCIA; ESTELA BORGMANN , MARTA; POSSATI SOUTO , LUIZA (Salão do Conhecimento, 2021)
Projeto de pesquisa realizado no projeto de extensão Cidadania Para Todos